2021
DOI: 10.1016/j.celrep.2021.108736
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin-mediated PPARγ S112 phosphorylation impairs IL-10 production and inflammation resolution during bacterial pneumonia

Abstract: Highlights d PPARg S112 phosphorylation is crucial for its K107 SUMOylation and IL-10 suppression d PIAS2 is the specific E3 SUMOligase causing CL-mediated PPARg K107 SUMOylation d JNK-MAPK is responsible for CL-mediated PPARg S112 phosphorylation d Repurposing a clinically used JNK inhibitor can improve survival in pneumonia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Instead, loss of TG2 delayed the rise in the CD206 mannose receptor [41], Arg1, GDF3, and IL-10-producing cells. Interestingly, the expression of all these factors is known to be regulated by PPARγ [7,42,43], a transcription factor playing a central role in the phenotypic switch of macrophages. Accordingly, we detected significantly lower PPARγ mRNA levels in the CD45 + cells derived from theTG2 null regenerating TA muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, loss of TG2 delayed the rise in the CD206 mannose receptor [41], Arg1, GDF3, and IL-10-producing cells. Interestingly, the expression of all these factors is known to be regulated by PPARγ [7,42,43], a transcription factor playing a central role in the phenotypic switch of macrophages. Accordingly, we detected significantly lower PPARγ mRNA levels in the CD45 + cells derived from theTG2 null regenerating TA muscles.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the role of Selenbp1 in cardiac fibrosis, we performed in vivo gene silencing using Selenbp1 siRNA (AM16830, Invitrogen) along with a transfection reagent, as previously described 25 but with some modification. Forty micrograms of siRNA combined with the non‐viral in vivo transfection reagent JetPEI® (Polyplus‐transfection) was administered three times every week to each rat through tail‐vein injection.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that genetic inhibition of PPARγ S112 increased adipogenesis (Ge et al, 2018;van Beekum et al, 2009), indicating an anti-adipogenic effect of PPARγ S112. Literature was also reported that PPARγ S112 phosphorylation impairs anti-inflammatory mechanism in bacterial pneumonia (Garg et al, 2021), which suggested its proinflammatory effect. However, we did not observe changes of PPARγ phosphorylation at S112 in the obese diabetic mouse brain where inflammation was presented.…”
Section: Discussionmentioning
confidence: 96%